Anticancer Properties of Macroalgae: A Comprehensive Review - Sara Frazzini; Luciana Rossi (Marine Drugs)
In recent years, the exploration of bioactive molecules derived from natural sources has gained interest in several application fields. Among these, macroalgae have garnered significant attention due to their functional properties, which make them interesting in therapeutic applications, including cancer treatment. Cancer constitutes a significant global health burden, and the side effects of existing treatment modalities underscore the necessity for the exploration of novel therapeutic models that, in line with the goal of reducing drug treatments, take advantage of natural compounds. This review explores the anticancer properties of macroalgae, focusing on their bioactive compounds and mechanisms of action. The key findings suggest that macroalgae possess a rich array of bioactive compounds, including polysaccharides (e.g., fucoidans and alginates), polyphenols (e.g., phlorotannins), and terpenoids, which exhibit diverse anticancer activities, such as the inhibition of cell proliferation, angiogenesis, induction of apoptosis, and modulation of the immune system. This review provides an overview of the current understanding of macroalgae’s anticancer potential, highlighting the most promising compounds and their mechanisms of action. While preclinical studies have shown promising results, further research is necessary to translate these findings into effective clinical applications.